2017
DOI: 10.1091/mbc.e16-06-0476
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Kif15 localization and motility by the C-terminus of TPX2 and microtubule dynamics

Abstract: Temporal and spatial regulation of mitotic motor proteins is required for proper spindle assembly and function. A single microtubule-associated protein, TPX2, regulates both kinesin-5 and kinesin-12 family members to support bipolar spindle formation and maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 52 publications
0
43
1
1
Order By: Relevance
“…However, in metazoan, kinesin-12 displays microtubule bundling and sliding activity. Recently, formation of tetrameric HsKif15 was reported also in vivo [53]. In vitro, dimeric HsKif15 promotes microtubule sliding of higher order microtubules utilizing a motile motor in concert with a non-motor microtubule binding domain [50].…”
Section: Pok2 Acts Redundantly With Pok1 In Division Site Maintenancementioning
confidence: 95%
See 1 more Smart Citation
“…However, in metazoan, kinesin-12 displays microtubule bundling and sliding activity. Recently, formation of tetrameric HsKif15 was reported also in vivo [53]. In vitro, dimeric HsKif15 promotes microtubule sliding of higher order microtubules utilizing a motile motor in concert with a non-motor microtubule binding domain [50].…”
Section: Pok2 Acts Redundantly With Pok1 In Division Site Maintenancementioning
confidence: 95%
“…Other in vitro studies report tetrameric HsKif15 switching between microtubule tracks and HsKif15 motor collectives that display processive movement at steady velocity [52]. Recently, formation of tetrameric HsKif15 was reported also in vivo [53]. Whether POK2 molecules form di-or tetramers and how these interact with microtubules requires further scrutiny.…”
Section: Pok2 Acts Redundantly With Pok1 In Division Site Maintenancementioning
confidence: 99%
“…The previously controversial question of the oligomerisation state of Kif15 under physiological conditions now seems settled, as motors within mitotic or interphase extracts were confirmed to be tetrameric by single molecule imaging (Mann, Balchand et al 2017). However it remains to be established whether the functional dimer-of-dimers of Kif15 is stabilised by parallel or antiparallel interactions, or indeed a mixture of the two, as in the Drosophila kinesin-5 tetramer (Scholey, Nithianantham We take this to mean that the functional unit in our optical trapping experiments is the twin heads of a tethered dimer.…”
Section: The Mechanics Of Kif15 Are Distinct From Those Of Kinesin-1 mentioning
confidence: 99%
“…Several cell biological studies have suggested that the functional redundancy of Kif15 with Eg5 might reflect a similar stepping mechanism and a similar action on microtubules (Tanenbaum, Macurek et al 2009, Vanneste, Takagi et al 2009). By contrast, recent in vitro reconstitution work on the action of single Kif15 tetramers on microtubules has revealed Kif15-specific behaviours (Drechsler, McHugh et al 2014, Drechsler and McAinsh 2016, Mann, Balchand et al 2017. Unlike Eg5 (Valentine, Fordyce et al 2006), Kif15 motors at zero load are highly processive, being capable of moving over 1μm along a microtubule before detaching.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation